"바일 벡터"의 두 판 사이의 차이

수학노트
둘러보기로 가기 검색하러 가기
(새 문서: ==메모== * http://www.math.harvard.edu/~kronheim/yaft.pdf * 각각의 $\alpha\in \Delta^+$에 대하여, $$ \begin{aligned} \omega_{\alpha}(\theta^{\vee}) & = \omega_{\alpha}(\sum_{...)
 
1번째 줄: 1번째 줄:
 
==메모==
 
==메모==
 
* http://www.math.harvard.edu/~kronheim/yaft.pdf
 
* http://www.math.harvard.edu/~kronheim/yaft.pdf
* 각각의 $\alpha\in \Delta^+$에 대하여,
+
* 각각의 <math>\alpha\in \Delta^+</math>에 대하여,
$$
+
:<math>
 
\begin{aligned}
 
\begin{aligned}
 
\omega_{\alpha}(\theta^{\vee}) & = \omega_{\alpha}(\sum_{\beta \in \Delta^+} n_{\beta}^{\vee} \beta^{\vee}) \\
 
\omega_{\alpha}(\theta^{\vee}) & = \omega_{\alpha}(\sum_{\beta \in \Delta^+} n_{\beta}^{\vee} \beta^{\vee}) \\
 
& = n_{\alpha}^{\vee},
 
& = n_{\alpha}^{\vee},
 
\end{aligned}
 
\end{aligned}
$$
+
</math>
$$
+
:<math>
 
\begin{aligned}
 
\begin{aligned}
 
\langle \omega_{\alpha},\theta \rangle &= \omega_{\alpha}(\theta^{\dagger}) \\
 
\langle \omega_{\alpha},\theta \rangle &= \omega_{\alpha}(\theta^{\dagger}) \\
14번째 줄: 14번째 줄:
 
& = \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee}
 
& = \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee}
 
\end{aligned}
 
\end{aligned}
$$
+
</math>
 
* 따라서  
 
* 따라서  
$$
+
:<math>
 
\begin{aligned}
 
\begin{aligned}
 
\langle \rho,\theta \rangle & = \langle \sum_{\alpha\in \Delta^+} \omega_{\alpha},\theta \rangle \\
 
\langle \rho,\theta \rangle & = \langle \sum_{\alpha\in \Delta^+} \omega_{\alpha},\theta \rangle \\
22번째 줄: 22번째 줄:
 
& = \frac{h^{\vee}-1}{2h^{\vee}}
 
& = \frac{h^{\vee}-1}{2h^{\vee}}
 
\end{aligned}
 
\end{aligned}
$$
+
</math>$

2020년 11월 16일 (월) 04:24 판

메모

\[ \begin{aligned} \omega_{\alpha}(\theta^{\vee}) & = \omega_{\alpha}(\sum_{\beta \in \Delta^+} n_{\beta}^{\vee} \beta^{\vee}) \\ & = n_{\alpha}^{\vee}, \end{aligned} \] \[ \begin{aligned} \langle \omega_{\alpha},\theta \rangle &= \omega_{\alpha}(\theta^{\dagger}) \\ & = \frac{\langle \theta,\theta \rangle}{2}\omega_{\alpha}(\theta^{\vee}) \\ & = \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee} \end{aligned} \]

  • 따라서

\[ \begin{aligned} \langle \rho,\theta \rangle & = \langle \sum_{\alpha\in \Delta^+} \omega_{\alpha},\theta \rangle \\ & = \sum_{\alpha\in \Delta^+} \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee} \\ & = \frac{h^{\vee}-1}{2h^{\vee}} \end{aligned} \]$